ANALYSIS OF VIRTUAL TOURISM OPPORTUNITIES IN KLAIPĖDA, LITHUANIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the current article the possibilities of virtual tourism in the city of Klaipėda are analysed. Over the past few decades, digital technology has helped the travel and tourism industry increase its reach. As the world faces the COVID-19 pandemic, virtual tourism has become relevant when the pandemic has made it more difficult to travel in real life. Therefore, it is important to determine whether the prospect of virtual tourism is visible in the city of Klaipėda, and to determine the possibilities of virtual tourism in the city of Klaipėda. The article reviews the concept of virtual tourism and virtual tourism technologies, analyses the idea of virtual tourism products, identifies the classification of virtual tourism products. The trends of virtual tourism in the world and in Lithuania are reviewed. The analysis is based on  a detailed analysis of scientific literature, journalistic articles and statistical data. A total of 137 publications were analyzed. Presenting virtual tourism products in Lithuania and the city of Klaipėda. The possibilities of virtual tourism and virtual tourism products of the city of Klaipėda are determined. Such results can be used as a positive role model of the small city virtual tourism attraction and system creation.